The Pyramiding of Three Key Root Traits Aid Breeding of Flood-Tolerant Rice - Chen Lin; Tongtong Zhu; Lucas León Peralta Ogorek; Youping Wang; Margret Sauter; Ole Pedersen (Plants, 2022)
Flooding is constantly threatening the growth and yield of crops worldwide. When flooding kicks in, the soil becomes water-saturated and, therefore, the roots are the first organs to be exposed to excess water. Soon after flooding, the soil turns anoxic and the roots can no longer obtain molecular oxygen for respiration from the rhizosphere, rendering the roots dysfunctional. Rice, however, is a semi-aquatic plant and therefore relatively tolerant to flooding due to adaptive traits developed during evolution. In the present review, we have identified three key root traits, viz. cortical aerenchyma formation, a barrier to radial oxygen loss and adventitious root growth. The understanding of the physiological function, the molecular mechanisms, and the genetic regulation of these three traits has grown substantially and therefore forms the backbone of this review. Our synthesis of the recent literature shows each of the three key root traits contributes to flood tolerance in rice. One trait, however, is generally insufficient to enhance plant tolerance to flooding. Consequently, we suggest comprehensive use of all three adaptive traits in a pyramiding approach in order to improve tolerance to flooding in our major crops, in general, and in rice, in particular.